2021
DOI: 10.1007/s10021-021-00697-7
|View full text |Cite
|
Sign up to set email alerts
|

Habitat Adaptation Mediates the Influence of Leaf Traits on Canopy Productivity: Evidence from a Tropical Freshwater Swamp Forest

Abstract: Functional traits offer generalizability to the prediction of ecosystem processes such as production, and community-weighted mean trait values are increasingly used for such predictions. However, the underlying causal direction between traits and ecosystem processes are often indirect and sometimes even tenuous. In this study, we aimed to uncover underlying causal mechanisms between traits, habitat adaptation and canopy productivity. We used canopy production data estimated from leaf litter traps, and trait an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…We did not find this, but instead found that swamp‐associated species had higher H max and lower D H . More importantly, our findings reinforce a recent study (Lam et al ., 2022) that showed that leaf traits may be as important as twig traits in conferring waterlogging stress tolerance to tropical forest tree species. This is likely because leaves and roots act as the water exchange surfaces of trees (root traits are likely to be important predictors of waterlogging stress tolerance as well; Kozlowski, 1997; Yamauchi et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not find this, but instead found that swamp‐associated species had higher H max and lower D H . More importantly, our findings reinforce a recent study (Lam et al ., 2022) that showed that leaf traits may be as important as twig traits in conferring waterlogging stress tolerance to tropical forest tree species. This is likely because leaves and roots act as the water exchange surfaces of trees (root traits are likely to be important predictors of waterlogging stress tolerance as well; Kozlowski, 1997; Yamauchi et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…low SLA, low leaf N, etc. ; Moor et al ., 2017; Mori et al ., 2019; Lam et al ., 2022) and xeromorphic traits (thick and sclerophyllous leaves with low transpiration rates; Lugo et al ., 1990). Many studies also find that tree species associated with wetland habitats have lower wood densities (Ordoñez et al ., 2010; Savage & Cavender‐Bares, 2012; McCoy‐Sulentic et al ., 2017; Moor et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have identified biochemical traits, such as nutrient concentrations and stoichiometric ratios, as being the strongest predictors of leaf litter decomposition, with physical traits being relatively less important (reviewed in Krishna & Mohan, 2017). By contrast, we found that few biochemical traits were important predictors of decomposability in our tropical freshwater swamp forest, except leaves with a higher CNR that had a slightly lower decomposability, in line with a previous bulk litter decomposition study at the same site (Lam et al ., 2022). Taken together, our findings suggest that decomposition in swamp forests differs from nonwetland forests in that oxygen availability to microbes, rather than nutrients, is likely to be more important in limiting litter decomposition rates.…”
Section: Discussionmentioning
confidence: 99%
“…Leaf litter for decomposition experiments, flammability experiments and litter trait measurements was collected between July 2020 and January 2021 from 10 replicate 400 m 2 long-term vegetation plots (from a total of 40 plots) established in 2013 (described in Chong et al, 2021;Lam et al, 2021Lam et al, , 2022. Freshly fallen leaf litter was collected from 1 m long × 1 m wide litter traps suspended at least 1 m above the ground on a fortnightly basis (Lam et al, 2021).…”
Section: Leaf Materials Collectionmentioning
confidence: 99%
See 1 more Smart Citation